2016
DOI: 10.1186/s40463-016-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival between radiation therapy and trans-oral laser microsurgery for early glottic cancer patients; a retrospective cohort study

Abstract: BackgroundThe literature reports various treatment methodologies, such as trans-oral laser microsurgery, radiation therapy, total/partial laryngectomies, and concurrent radiation chemotherapy for patients with early larynx cancer. However, at the forefront of early glottis treatment is trans-oral laser microsurgery and radiation therapy, likely due to better functional and survival outcomes. Here we conduct the largest Canadian head-to-head comparison of consecutive patients treated with either radiation thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
(10 reference statements)
2
18
0
1
Order By: Relevance
“…A study of 75 patients by De Santis et al found no difference in 5-year diseasefree survival, overall survival, or laryngeal preservation for patients with T1 and T2 carcinoma treated with TLM versus radiation. 19 A meta-analysis of voice outcomes by Greulich et al showed similar subjective and objective outcomes between TLM and EBRT. 20 One of the ongoing goals in management of laryngeal cancer is stratification of patients into high-and low-risk groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study of 75 patients by De Santis et al found no difference in 5-year diseasefree survival, overall survival, or laryngeal preservation for patients with T1 and T2 carcinoma treated with TLM versus radiation. 19 A meta-analysis of voice outcomes by Greulich et al showed similar subjective and objective outcomes between TLM and EBRT. 20 One of the ongoing goals in management of laryngeal cancer is stratification of patients into high-and low-risk groups.…”
Section: Discussionmentioning
confidence: 94%
“…However, this analysis did not take into account clinical and demographic factors of each patient group, and the local control rate was not significantly different between the two groups. A study of 75 patients by De Santis et al found no difference in 5‐year disease‐free survival, overall survival, or laryngeal preservation for patients with T1 and T2 carcinoma treated with TLM versus radiation . A meta‐analysis of voice outcomes by Greulich et al showed similar subjective and objective outcomes between TLM and EBRT …”
Section: Discussionmentioning
confidence: 99%
“…Among LSCCs, glottic cancer is the most common subtype, accounting for 80% of LSCC patients in the current study. Several studies have concluded that surgery is associated with a higher survival in patients with LSCCs, while there are a number of studies that have reported the opposite results; however, most of these studies were based on <100 patients . In a large meta‐analysis that included 562 participants treated with laser surgery and 706 participants treated with radiotherapy, the pooled analysis showed that laser surgery significantly improved the overall survival of patients with T1 glottic carcinoma group .…”
Section: Discussionmentioning
confidence: 99%
“…The patients were divided into two groups: the radiotherapy group and the laser-ablation group. The 5-year DSF rates of the two groups were 90.8% and 93.3%, respectively, and there were no significant differences in the 5-year LC or PFS rate [2]. A review in Martine 2017 described a comparison of treatments for T2 disease, and 48 studies showed no significant differences between radiotherapy (n=3191) and TLM (n=1156) at 5 years (75.81% vs 77.26%) [7].…”
Section: Discussionmentioning
confidence: 95%